Factibilidad para la creación de un centro recreativo y turístico para el Gobierno Autónomo Descentralizado del cantón El Empalme - Reyes Saltos, Brenda Giomara (2012)
Tourism in Ecuador is an activity that has grown steadily worldwide in recent years, as evidenced by the latest estimates of world tourism organization (WTO), and that even is the activity that best responds to the effect of the crisis, as evidenced in the indicators of the balance of payments and national accounts in the countries of the Andean Region, among which is our country. It was considered important to investigate the issue of tourism in the city’s El Empalme, to know and appreciate their natural beauty determine the preferences of the population to visit these places, and assess their impact on the local development process, this certainly justify its elaboration because it is an activity and sector where there is much to be done. The analysis of the problem made it possible to formulate the objectives of the research and propose the creation of alternative recreational and tourist center in the river Macul. The field research was conducted through surveys and interviews applied to the selected sectors (population and authorities of the canton municipal El Empalme GAD), results and information that were submitted for discussion to establish the incidence of weaknesses in the development of tourism and to highlight their potential to benefit the local economy, which also allowed the hypothesis raised in the investigation. We performed a feasibility study technical, economic, financial, administrative and environment impact of recreational and tourist center of the river Macul to determine its viability. The conclusions reached during the investigation, determined to achieve the objectives, the impact caused by the lack of attention of the authorities, and the preferences of the visitors to know and perform a type of recreational tourism. The recommendations were made considering the degree of social and political responsibility of the actors involved, in order to agree interests tend to value tourism as a development alternative, generation of resources and creation of jobs. The proposed construction of recreational and tourist Macul river, through the feasibility study demonstrated that if you can do.